An audit of the use of hydroxychloroquine in rheumatology clinics - Worth, C; Yusuf, IH; Turner, B; Gourier, H; Brooks, EE; Mort, DO; Sharma, S; Downes, SM; Luqmani, RA (Oxford University Press, 2018)
Objectives To audit the use, indications, complications and patient information regarding hydroxychloroquine (HCQ) treatment in rheumatology clinics in a tertiary referral centre. Methods During a 9-month period, we identified all patients prescribed HCQ and attending rheumatology clinics in one hospital. We established: (1) the indication for HCQ (2) the prevalence of HCQ overdosing based on absolute body weight (ABW) (3) documentation of warning of risk of retinal toxicity (4) systemic and ocular co-morbidities (5) ocular symptoms during treatment (6) reasons for stopping HCQ. Results We identified 427 patients (104 male, 323 female). The cumulative dose of HCQ was lower in rheumatoid arthritis (RA; median 365 g; range 6-1752 g) compared to systemic lupus erythematosus (SLE; 450 g; 66-1788 g) (p = 0.105). The median duration of HCQ therapy was four years (range 0.1-13); 28% of patients with RA and 29% with SLE continued HCQ beyond five years. After adjusting for ABW and renal function, 10% (31/312) had been prescribed doses exceeding recommendations. Formal documentation of counselling on ocular complications was only found in one third of patients. Three cases of HCQ retinopathy were identified (all of whom had RA). Conclusion HCQ therapy is being used for more than five years in 29% of patients with rheumatic diseases, with higher than recommended doses in approximately 10% of patients. We recommend more rigorous scrutiny of the use of HCQ to reduce the risk of retinopathy.